Carbonyl compounds as cathode materials for lithium-ion batteries - Choo, Kenneth Wei Jie (2017)
Organic compounds as active electrode materials are known for their low cost, versatility, renewability and eco-friendliness. Carbonyl compounds with large aromatic structure and heteroatoms have proven to achieve long cycling stability and high specific capacity. In this report, a novel carbonyl compound with heteroatoms and large aromatic structures (PDA-4N) was investigated as cathode material for lithium-ion battery. Electrochemical properties of PDA-4N of different weight ratio and NTCDA were evaluated and discussed. The active materials were well blended with CNT additive and PVDF binder before establishing a coin-type cell configuration for analyses on cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), rate performance, cycling performance and charge-discharge capacity profile. Investigations on electrochemical performances of PDA-4N were conducted between 2.0 and 3.9V vs. Li/Li+. PDA-4N demonstrated a reasonably high initial specific capacity of 116.3 mAh g-1 and rate performance up to current rate of 7.92C. PDA-4N also exhibited a stable cycling performance of 50 cycles with reasonable capacity retention of 78.7% of its theoretical capacity and a high coulombic efficiency of 99.86% on average. However, EIS measurement revealed that PDA-4N possessed slow charge transfer capability and poor electric response. Further studies on CNT additive and PVDF binder ratio illustrated a positive effect on cycling stability of PDA-4N. This study reveals that carbonyl compound with heteroatoms and large aromatic structures could potentially be utilised as organic cathode material for rechargeable lithium-ion battery and effective modifications can be made to further enhance the electrochemical properties.